On componential analysis as a valid pedagogic tool for vocabulary instruction in foreign language teaching - Porto, Melina (1999)
The aim of this paper is to explore the role of Componential Analysis in vocabulary teaching in the context of foreign language instruction. A fruitful line of inquiry is to consider whether vocabulary deserves separate pedagogic treatment in the language classroom and if so, to inspect whether Componential Analysis proves advantageous. The pa per is divided into two sections. Section I presents the theoretical foundations for the claim that vocabulary is not peripheral but central in language teaching. Section II examines the advantages and disadvantages of Componential Analysis as a framework to orchestrate vocabulary teaching practices. Theoretical considerations, pedagogic implications and some practical applications are explored.